If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2g + 15 = 10 + -1(-4g + -1) Reorder the terms: 15 + -2g = 10 + -1(-4g + -1) Reorder the terms: 15 + -2g = 10 + -1(-1 + -4g) 15 + -2g = 10 + (-1 * -1 + -4g * -1) 15 + -2g = 10 + (1 + 4g) Combine like terms: 10 + 1 = 11 15 + -2g = 11 + 4g Solving 15 + -2g = 11 + 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 15 + -2g + -4g = 11 + 4g + -4g Combine like terms: -2g + -4g = -6g 15 + -6g = 11 + 4g + -4g Combine like terms: 4g + -4g = 0 15 + -6g = 11 + 0 15 + -6g = 11 Add '-15' to each side of the equation. 15 + -15 + -6g = 11 + -15 Combine like terms: 15 + -15 = 0 0 + -6g = 11 + -15 -6g = 11 + -15 Combine like terms: 11 + -15 = -4 -6g = -4 Divide each side by '-6'. g = 0.6666666667 Simplifying g = 0.6666666667
| 7x-6=-5x-3 | | 7(x+8)-14=28 | | .6x-7=7 | | 4x-80=0 | | 55x+3(9x+12)=-64 | | 0=16t^2+128t+144 | | x+3.8=9.2 | | 4p+2p+6p-1= | | 7x-20=29 | | Ma-Th=fun | | -10x+10=-10 | | (4x^2)(-2x^3y^5)(-3xy)=0 | | 5x*5x= | | r(x)=-0.11x^2+100x | | 5n-18=-33 | | -5x+-30=80 | | 3(5z-3)-3(-2z)=6 | | 2(x-1)=3x-(x+2) | | 6s-15=-6+5a | | 9t-22=-29+8t | | -11x-31=-20 | | .5y+7=.75y-4 | | 32=(x-7)(x+7) | | 5(6c-4)+3(8c-1)= | | 2(3+5x)-5=31 | | 74-4x=14x+24 | | 15-2(w+5)=11 | | X+24=130 | | 11x-31=-20 | | x+9.8=14.5 | | 7=y-12 | | 3x-17=16-(2x+8) |